PENGARUH KUALITAS LAYANAN, HARGA DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA PENGGUNA GRABFOOD (STUDI KASUS MAHASISWA PROGRAM STUDI MANAJEMEN ANGKATAN 2022-2023 UNIVERSITAS METHODIST INDONESIA) - Rapika Natalia Tambunan; Siti Normi; Maludin Panjaitan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the simultaneous effect of Service Quality, Price, and Promotion on Customer Satisfaction among GrabFood users who are students of the Management Study Program, Class of 2022–2023, at the Indonesian Methodist University. The research methodology used in this study is a quantitative descriptive research method. The sample in this study consisted of 227 respondents. Based on the results of the t-test hypothesis, it can be concluded that service quality partially has a positive and significant effect on user satisfaction, price partially has a positive and significant effect on user satisfaction, and promotion partially has a positive and significant effect on user satisfaction. Based on the results of the F hypothesis test, it can be concluded that service quality, price, and promotion simultaneously have a positive and significant effect on customer satisfaction. Based on the analysis of the coefficient of determination, an Adjusted R Square value of 0.608 was obtained. This means that 60.8% of the variation in customer satisfaction can be explained by service quality, price, and promotion, while the remaining 39.2% is influenced by other factors outside this study.